The Perception of Bilingual Songs in Slovenia and the Cultural Dimensions of Language Selection - Klobčar, Marija (Tautosakos darbai, 2020)
This article identifies the circumstances in which bilingual songs in Slovenia existed and follows the changes in the songs’ social role from the first half of the 19th century to the period after the end of the Second World War. It follows these changes as they occurred within the framework of folkloristics and in the practices that folklore scholars tried to shape and those that continued without intervention. In order to discern the circumstances in which bilingual songs were created, the author focuses on two songs that were documented by one of the first collectors and researchers of Slovenian folk songs, Stanko Vraz. These are the German-Slovenian toast song “Seid fröhlich, ihr Brüder”, which only rarely appears in later records, and a Slovenian song “Kam bova vandrala vandrovček moj” (‘Whither Shall we Wander, my Little Wanderer?’), which transcribers encountered in different dialects or supradialects. This song appears in the records as a bilingual, Slovenian-German song only later, in the 20th century. The author explores which social groups were characterized by bilingual songs and whether the negative attitude of folkloristics to these songs directed and changed only a selection of folk songs made by collectors, or the repertoire of singers as well.